Challenging the 'Native Speaker' Ideal: The Impact of Native Speakerism on Language Education - Dey, Manna; Amelia, Rizky; Herawati, Yayuk Widyastuti (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2023)
Native-Speakerism has emerged as a prominent element of contemporary TESOL discourse and a frequent talking point when it comes to issues of language-related prejudice and discrimination. It does so by building on a diverse range of sources and intentionally slanting toward amusing the trendy. It is suggested that the ideological conception of native-speakerism applies retroactively to the coveted victimization and the narrative of indignation that goes along with it to people who identify as "non-native speakers.” The researchers used a literature review through six steps to unravel challenging the native speaker ideal: the impact of native speakerism on language education. The reason behind choosing this topic is to find out how deep the ideology of getting advantages that the native-speakers are having in every stage where the non-native speakers are having trouble including different perspectives as well. It is shown how the fortress of victimization then allows those inside through or the people who have been harmed. In this article, the distinction between native and non-native speakers in terms of teaching and learning the English language, The idea that a "native speaker" is inherently more competent to instruct English than a "non-native speaker" is known as the "native speaker's fallacy" as well as strengths and weaknesses of both the characteristics shall be described in detail.